The impact of blockchain on e-commerce: A framework for salient research topics - Treiblmaier, Horst; Sillaber, Christian (Electronic commerce research and applications, 2021)
•The first academic paper that presents a comprehensive research agenda for the implications of Blockchain (DLT) on e-Commerce.•The framework contains technological, legal, organizational and consumer issues.•Blockchain (DLT) is shown as a decisive factor for e-commerce success.•Detailed research questions that need to be tackled in order to systematically explain, explore and predict the impact of Blockchain (DLT) on e-commerce. Blockchain-based technologies are predicted as major disruptors for numerous business applications and processes, which bears huge implications for e-commerce. Given the ability of blockchain and related technologies to create so-called “trustless systems” with idiosyncratic properties, various business models and established processes that have emerged over the years to ensure trust, reliability and enforceability in business-to-consumer (B2C), business-to-business (B2B), business-to-government (B2G) and consumer-to-consumer (C2C) relations need to be questioned and potentially adjusted. Blockchain has the potential to shake the foundation of e-commerce by enabling exchange relations that are trustless and operate without dedicated intermediaries or even central authorities in the case of permissionless blockchains. Furthermore, the exchange of information and value between companies and consumers might change considerably by enabling unified access to immutable data along the entire supply chain. In this paper, a framework and 19 high-level research questions are developed to inspire researchers to closely investigate the potential impact of blockchain on e-commerce. The main categories include (a) technological, (b) legal and (c) organizational and quality issues as well as (d) consumer issues. This paper illustrates how blockchain potentially impacts different elements of e-commerce in these respective areas.